2020
DOI: 10.1097/md.0000000000021290
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and outcomes of 2 therapeutic interventions for cardiac tamponade

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Existing data comparing mortality after PC and SD are mixed. In studies examining the management of cardiac tamponade, both Allen et al and Zgheib et al found an approximate 4–5% increase in mortality following PC compared to SD [ 8 , 17 ]. In contrast, several other studies found no difference in mortality between the two treatment strategies [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing data comparing mortality after PC and SD are mixed. In studies examining the management of cardiac tamponade, both Allen et al and Zgheib et al found an approximate 4–5% increase in mortality following PC compared to SD [ 8 , 17 ]. In contrast, several other studies found no difference in mortality between the two treatment strategies [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current era of value-based medicine, there is a growing emphasis on delivering optimal care while minimizing healthcare-related costs. A recent study by Zgheib et al found cardiac tamponade patients treated with SD to have lower mortality rates but longer length of stay and higher healthcare expenses [ 17 ]. Our study expands upon these findings in a larger, more contemporary cohort and includes long-term readmission outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study based on US Nationwide Emergency Department Sample database, tamponade patients treated with surgical pericardiotomy had lower mortality rates but longer length of stay and higher health care expenses. 24 There is need for defining easily reproducible CT criteria to standardize reporting of PeEff on CT similar to echocardiography. Standardized objective and subjective CT criteria can be used to more effectively compare the findings with echocardiography, and document disease resolution or progression.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of cardiac tamponade is essential as these patients may require urgent percutaneous pericardiocentesis or surgical pericardiotomy. In a recent study based on US Nationwide Emergency Department Sample database, tamponade patients treated with surgical pericardiotomy had lower mortality rates but longer length of stay and higher health care expenses 24 …”
Section: Discussionmentioning
confidence: 99%
“…However, for those patients in whom this procedure is indicated, there are two methods of pericardial drainage: pericardiocentesis (PCC) and surgical pericardiotomy (SP). Previous studies have shown that the survival rates of PCC and SP are comparable [5][6][7][8] ; the survival rate of SP is higher 9 in patients with endogenous disease, but these patients cannot be considered to have trauma because of differences in the underlying disease and nature of the fluid reservoir. There are a few small studies on cases of blunt traumatic cardiac tamponade [10][11][12][13][14] and the evidence is insufficient.…”
Section: Introductionmentioning
confidence: 99%